ارتفاع المعتدلات وقصور القلب بعد احتشاء العضلة القلبية الحاد - رضوان عبد الناصر; بله حسام; اسماعيل حسان (Latakia University Journal -Medical Sciences Series, 2019)
أرضية الدراسة: إنَّ الالتهاب المترافق مع احتشاء العضلة القلبية الحاد يترافق بشكل متكرر مع كثرة الكريات البيض المحيطية وارتفاع المعتدلات النسبي. هدف الدراسة: هو تحديد الترافق بين تعداد الكريات البيض في الدم المحيطي والنسبة المئوية للمعتدلات عند القبول في المشفى وبين التطور اللاحق لقصور القلب التالي للاحتشاء حيث تضمنت الدراسة /70/ مريض مصاب باحتشاء عضلة قلبية حاد في مشفى الأسد الجامعي باللاذقية بين عامي 2003-2004. الطرق والنتائج: تم إجراء ايكو قلب للمرضى في اليوم الرابع من احتشاء العضلة القلبية الحاد ودراسة الوظيفة الانقباضية والانبساطية ودراسة العلاقة بين تعداد الكريات البيض الكلي والنسبة المئوية للمعتدلات وتطور قصور القلب في الأيام الأربعة الأولى من الاحتشاء. حيث أن 41.4% من المرضى لديهم تعداد كريات بيض محيطي مرتفع < 109×11/ل، 55.7% منهم لديهم معتدلات < 65% و60% منهم لديهم نقص نسبي في اللمفاويات ≤ 25%. قصور القلب الانقباضي تطور عند 27 مريض (38.5%)، 24 مريض (89%) لديهم ارتفاع معتدلات < 65% مقارنة مع 15 مريض من أصل 43 (34.8%) من الذين لم يتطور عندهم قصور القلب. لا توجد علاقة هامة بين ارتفاع المعتدلات وبين سوء الوظيفة الانبساطية. التعليق: إن الارتفاع النسبي للمعتدلات عند القبول في المشفى لمرضى الاحتشاء الحاد تترافق بشكل باكر مع قصور القلب الانقباضي. هذا الترافق قد يساعد في تحديد الحالات ذات الخطورة العالية والتي يمكن أن يقدم لها العون بتداخلات أكثر هجومية لمنع أو انقاص خطورة قصور القلب. Background: inflammation associated with acute myocardial infarction (AMI) is frequently marked by a peripheral leukocytosis and relative neutrophilia. The objective of this study: is to examine the association between hospital admission peripheral total leukocyte count and the neutrophil percentage and the subsequent development of heart failure in patients with (AMI). This study included /70/ patients of (AMI) who have been admitted in AL-Assaed University Hospital in Lattakia between 2003-2004. Methods and results: Echocardiography has been performed for each patient in the four days after (AMI), Systolic and diastolic function have been evaluated, then we examine the relation between the total leukocyte count, neutrophil percentage and the development of heart failure in the first 4 days after (AMI). 41.4% of the cohort had a leukocyte count > 11x109/L on admission to the Hospital; 55.7% had a neutrophil percentage > 65% and 60% had a lymphocyte percentage ≤ 25%. Systolic heart failure developed in /27/ patients (38%) of the cohort, of these 24 patients (89%) had relative neutrophilia (neutrophil percentage > 65%) compared with /15/ patients (24.8%) of those in whom systolic failure didn’t develop. There is no relation between neutrophilia and diastolic dysfunction. Conclusion: relative neutrophilia on admission to the hospital in patients with (AMI) is significantly associated with the early development of systolic heart failure. This association may help in the identification of individuals of high risk who might benefit from more aggressive interventions to prevent or reduce the risk of heart failure.